The directive politeness level through a test approach completing the Arab Village community discourse - Parwanti, Sri; Rusli, Ris'an; Dungcik, Masyhur (International Journal Labs, 2024)
This study aims to understand and describe the realization of language politeness in the people of Sei Bayas Arab Village in Palembang City. The study is based on data from the Complete Discourse Test which was distributed to 40 residents living on the Sei bayas Arabic campus. The results show that the respondents use a variety of strategies, including indirect speech, fenced speech, and words that express respect, to communicate their requests and expectations. The respondents used minimizing losses, disclosing face-threatening acts, and revealing that they owe favor to their speech partners.